Assessment of licensed indigenous midwives’ knowledge concerning prevention and management of postpartum hemorrhage in Baghdad city - Jaber, eman; Abbas, Iqba (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): The aim of this study is to assess licensed indigenous midwives’ knowledge concerning prevention andmanagement of postpartum hemorrhage in Baghdad City.Methodology: A descriptive analytic study is conducted on a purposive "non-probability" sample of one hundredlicensed indigenous midwives who were selected what represents 26% of the target population, during period fromMarch, 5th to May, 10th,2008. The study is conducted at the two settings of Ministry of Health (Baghdad healthdirectorate in Al-Karhk and Al-Risafa) sector during their annual renewed license for midwifery practice. Thequestionnaire form is consisted of three parts which included demographic data, knowledge concerning preventionand management of primary postpartum hemorrhage. Content validity and reliability of the questionnaire isdetermined through a pilot study, descriptive and inferential statistical are used to analyze the data.Results: The study results showed that the highest percentage (40%) of study sample is of the age group (50-59 years)and more than half of the study sample is primary school graduate and less. More than the half of the study sample isassigned to primary postpartum hemorrhage during their practices in midwifery. There were statistically significantrelationships between knowledge of licensed Indigenous Midwives regarding prevention and management of primarypostpartum hemorrhage and their ages and level of education.Recommendations: The study recommends that licensed indigenous midwife should be provided with information onsafe delivery practices and the importance of healthy referral system. Committing licensed indigenous midwife toapply Ministry of Health instructions, do not allowing delivering risky pregnant cases. Establish midwifery departmentfor medical technical institutes and higher diploma degree in midwifery for college nurse graduates